Plots against Russia : conspiracy and fantasy after socialism - Borenstein, Eliot, 1966- (Cornell University Press, 2019)
"A study of paranoid, conspiratorial, and extremist trends in Russia's media, film, and fiction since the collapse of the Soviet Union"--